2018
DOI: 10.1155/2018/2315372
|View full text |Cite
|
Sign up to set email alerts
|

Trend and Abrupt Regime Shift of Temperature Extreme in Northeast China, 1957–2015

Abstract: Trend and an abrupt regime shift of temperature extremes were investigated based on diurnal data at 116 meteorological stations in the Northeast China region during 1957-2015. A total of 10 temperature indices divided into two categories: extremely cold and warm indices, were used in this study. e Mann-Kendall (MK) test was employed to evaluate the trend in temperature while changepoint, an R package for changepoint analysis, was used to detect changes in the mean levels of temperature extreme data series. e r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…On the whole, the wetland loss rate would be 0.9 and 7.4% under RCP 2.6 for the 2050s and 2070s and would be 6.3 and 23.8% under RCP 8.5 for the 2050s and 2070s, respectively. Recent studies have shown that the Xing'anling Mountains have been stalled in a climate warming stage from 1957 to 2015, the annual average temperature in this period was approximately −3.22°C (Mwagona, Yao, Shan, Yu, & Zhang, 2018; Zhao et al, 2016). More seriously, this climate warming trend in the Xing'anling Mountains is predicted to continue and even accelerate during the 21st century (Hjort et al, 2018; Sun, Miao, & Duan, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…On the whole, the wetland loss rate would be 0.9 and 7.4% under RCP 2.6 for the 2050s and 2070s and would be 6.3 and 23.8% under RCP 8.5 for the 2050s and 2070s, respectively. Recent studies have shown that the Xing'anling Mountains have been stalled in a climate warming stage from 1957 to 2015, the annual average temperature in this period was approximately −3.22°C (Mwagona, Yao, Shan, Yu, & Zhang, 2018; Zhao et al, 2016). More seriously, this climate warming trend in the Xing'anling Mountains is predicted to continue and even accelerate during the 21st century (Hjort et al, 2018; Sun, Miao, & Duan, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Donat et al, 2013). Mwagona et al (2018) observed changes in cold/warm night frequency at 116 stations in northeastern China. They report a decrease in cold night frequency during winter and spring, while warm night frequency increased primarily in summer.…”
Section: Frequencymentioning
confidence: 99%
“…Matthews et al, 2016b) in a given period. The number of events can be estimated using tracking algorithms, ranging from simple algorithms based on the mean sea level pressure values for cyclone activity (Murray and Simmonds, 1991;Donat et al, 2011) and the exceedance over the 98th percentile wind speeds for wind storms (Leckebusch et al, 2008) to the more complex tracking of sting jets (Hart et al, 2017). The frequency of extreme winds may be quantified from reanalysis data, noting that the trend magnitude and sign can be sensitive to the reanalysis product (Befort et al, 2016;Wohland et al, 2019;Torralba et al, 2017).…”
Section: Frequencymentioning
confidence: 99%
“…Many scholars have studied the variation of temperature in northeast China. Mwagona et al [21] found that T min increased at a faster rate than T max , leading to the decrease of DTR in northeast China. Shen et al [22] obtained similar results using data from meteorological stations.…”
Section: Introductionmentioning
confidence: 99%